Analysis of The Corona Virus Outbreaks Short-Term Effects on Indonesias Economy and Poverty - Saiful Adhi Saputra; Karta Sedyatmo (Ideas Publishing, 2022)
The goal of this study is to look at the short-term effects of the coronavirus epidemic in Indonesia on the economy and poverty. The Indonesian government has enacted many policies to limit the incidence of coronavirus transmission in the country, however, these efforts have had a significant impact on the countrys economy and poverty. Indirectly, the coronavirus pandemic harmed Indonesias economic sector. This viral epidemic has reduced job prospects, raised unemployment, and led some sectors to shut down, resulting in a drop in peoples earnings and spending power. Furthermore, the Indonesian economy was hit by a downturn, which pushed up the poverty rate. The coronavirus outbreak has an immediate impact on all levels of society and diverse groups; nevertheless, the IMF expects that the impact of this virus outbreak will endure for a long period, implying that this virus will have a long-term influence. The Indonesian government has implemented several policies that are causal in suppressing the corona viruss transmission, such as health protocols, large-scale social restrictions (PSBB), and restrictions on community activities (PPKM), as well as policies for community economic recovery and poverty alleviation, such as the distribution of fast and medium-term social assistance, as well as capital assistance. The governments program is projected to minimize the rate of coronavirus transmission and restore economic mobility in Indonesia, as well as address the problem of poverty, particularly among those affected by the corona virus epidemic. Tujuan dari penelitian ini adalah untuk melihat dampak jangka pendek dari wabah virus corona di Indonesia terhadap perekonomian dan kemiskinan. Pemerintah Indonesia telah mengeluarkan banyak kebijakan untuk membatasi kejadian penularan virus corona di negara ini, namun upaya tersebut berdampak signifikan terhadap perekonomian dan kemiskinan negara. Secara tidak langsung, pandemi virus corona merugikan sektor ekonomi Indonesia. Epidemi virus ini telah mengurangi prospek pekerjaan, meningkatkan pengangguran, dan menyebabkan beberapa sektor ditutup, mengakibatkan penurunan pendapatan dan daya beli masyarakat. Lebih jauh lagi, perekonomian Indonesia mengalami keterpurukan yang mendorong naiknya angka kemiskinan. Wabah virus corona berdampak langsung pada semua lapisan masyarakat dan kelompok yang beragam; namun demikian, IMF memperkirakan dampak wabah virus ini akan bertahan lama, menyiratkan bahwa virus ini akan memiliki pengaruh jangka panjang. Pemerintah Indonesia telah menerapkan beberapa kebijakan yang bersifat kausal dalam menekan penularan virus corona, seperti protokol kesehatan, pembatasan sosial berskala besar (PSBB), dan pembatasan kegiatan masyarakat (PPKM), serta kebijakan pemulihan ekonomi masyarakat dan kemiskinan. pengentasan, seperti penyaluran bansos cepat dan jangka menengah, serta bantuan permodalan. Program pemerintah tersebut diproyeksikan untuk menekan laju penularan virus corona dan memulihkan mobilitas ekonomi di Indonesia, serta mengatasi masalah kemiskinan, khususnya di antara mereka yang terkena dampak epidemi virus corona.